Comparative analysis of English and Uzbek folktales - Amanova, Onarxol (The Lingua Spectrum, 2025)
Abdulla Aripov said that "Wisdom belongs to the East." In fact, the spirit of admonition predominates in the lower part of the songs written by us, the Eastern peoples. This article compares folk tales and culture, one of the world's oldest and richest forms of oral literature, and explores the importance of fairy tales in human and social life. This article examines the English folk tale "The Leopard Woman" The article points out that any difficulty that may arise in life should be overcome by both husband and wife. If all the work is put on the woman, it can sometimes lead to evil. It is stated that it is not good to put pressure on one person in the family and that there is a limit to endurance. The essence of the fairy tale and its comparative artistic ideological aspects are analyzed. The tale points out the need to speak carefully understand and respect each other in family relationships. Also, the analysis of the English folk tale is aimed at forming a spiritual and enlightening worldview. In general, learning the language with the help of English folk tales is also effective. Information is provided on the comparative analysis of the content of the Uzbek folktale and the English folktale.